Reconciling macroeconomic determinants with stock market performance in selected Sub-Saharan African countries: An ARDL approach - Kareem Abidemi Arikewuyo; Akeem Adekunle Adeyemi; Eunice Titilayo Omodara; Lateef Adewale Yunusa (Journal of Banking and Financial Economics (JBFE), 2020)
Prior studies have adduced unstable macroeconomic factors to stock price movement overtime but the relationship between the duo remained unsettled. Autoregressive Distributed Lag (ARDL) technique was used to reconcile the macroeconomic determinants with performance of stock markets in selected Sub-Saharan Africa (SSA) covering the period of 1999:1-2017:4. It was found that macroeconomic indicators were essential in determining stock market performance in Nigeria while South African stock market did not show any predictable linkage but the contemporaneous effect of oil price changes on stock market performance in selected SSA. The study, therefore, recommended that countries in SSA should reduce overdependence on oil to minimize external influence in order to promote stability of the stock markets.
Keywords: E6; G1; R5; 330; Macroeconomic Determinants; Stock Market Performance; External Shock; Sub-Saharan Africa